Human Rights for Information in Social Networks: Constitutional Aspect - Byelov, Dmytry (Journal of Legal Studies, 2018)
The article is devoted to coverage features the use of public information in social networks. The author draws attention to the occurrence of criminal responsibility for public expression in social networks.